تأثير الثقافة التنظيمية على إتجاهات الجمهور الداخلي دراســة ميدانيــة بمؤسسة الدهن – وحدة سـوق أهـراس - سناني سمية; قروي جميلة (My University, 2017)
Study Summary: Through our study of the topic of “The Impact of Organizational Culture on Internal Audience Attitudes,” we sought to investigate one of the issues that arises, namely the importance of organizational culture and the need to modify the trend, given its importance to organizations that still have a dire need to study organizational belonging and loyalty among employees. Therefore, the need to research increasing the effectiveness of the communication process has increased, within the framework of achieving high organizational loyalty, and thus a unique organizational culture. ---------------------- ملخص الدراسة: من خلال دراستنا لموضوع "تأثير الثقافة التنظيمية على اتجاهات الجمهور الداخلي"، سعينا إلى دراسة إحدى القضايا المطروحة، ألا وهي أهمية الثقافة التنظيمية وضرورة تعديل هذا التوجه، نظرًا لأهميتها للمؤسسات التي لا تزال بحاجة ماسة إلى دراسة الانتماء والولاء التنظيمي لدى موظفيها. لذلك، ازدادت الحاجة إلى البحث في كيفية زيادة فعالية عملية الاتصال، في إطار تحقيق ولاء تنظيمي عالٍ، وبالتالي ثقافة تنظيمية فريدة.
Keywords: الثقافة التنظيمية، إتجاهات الجمهور الداخلي